Consumer Protection Education: Preventive Measures Against Online Transaction Problems for Students of SMAN 8 Pinrang: Edukasi Perlindungan Konsumen: Upaya Preventif terhadap Permasalahan Transaksi Online bagi Siswa SMAN 8 Pinrang - Amaliyah, Amaliyah; Rifai, Aulia; Marwah, Marwah; Kurniawati, Andi; Aswan, Muhammad; Hamdani, Khulaifi; Mada, Ahkamul Ihkam (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
As a country with a high number of internet users, online activities such as shopping have become a trend among students. However, these transactions are often accompanied by legal issues, such as receiving items that do not match the description, delayed deliveries, defective products, and uncertainties regarding returns. These problems result in losses for buyers, mainly due to their lack of understanding of consumer rights and business obligations. To address these challenges, this community service activity was conducted with the aim of enhancing students' understanding of consumer rights in online transactions, as well as their knowledge of the obligations and restrictions for business actors, in order to minimize both material and immaterial losses. This community service was carried out at SMAN 8 Pinrang using a double blended method, combining quantitative and qualitative approaches through three stages of counseling: pre-test, material presentation, and post-test. During the counseling sessions, students were provided with explanations regarding consumer rights and legal protections in online transactions. The results showed a high level of enthusiasm from participants, as well as a significant increase in their understanding of consumer rights and business obligations after the activity. Based on the post-test results, students' understanding of consumer rights increased from 0% to 100%, and all participants were also able to understand the restrictions that business actors must follow. The implications of this activity demonstrate that consumer protection legal education is effective in raising students' legal awareness and equipping them with the ability to address online transaction issues more critically and responsibly